Pemanfaatan Limbah Kulit Udang Sebagai Edible Coating Chitosan Dalam Menghambat Kemunduran Mutu Fillet Ikan Kakap Skinless - Belvi Vatria; Vivin Primadini; Kristina Novalina (Jurnal Kelautan, Lingkungan, dan Perikanan, 2021)
In general, the purpose of this study was to utilize shrimp shell waste as an edible coating of chitosan in inhibiting the deterioration of the quality of skinless snapper fillets. This research is an experimental research using factorial completely randomized design with two treatment factors, namely the concentration factor of the chitosan coating solution with 3 levels, namely 1%, 2%, and 3%, and the immersion time factor with 2 levels, namely 1 minute and 3 minutes. The data were processed statistically with analysis of variance and Duncan's continued test if the results were significantly different. The results of the study found that the characteristics of chitosan made from waste vanamie shrimp shells met the predetermined quality standards. Skinless snapper fillets continued to decline in quality as storage time increased. However, skinless snapper fillets that were treated with chitosan edible coating experienced a slower decline in quality compared to untreated skinless snapper fillets. The treatment chosen as an ingredient for chitosan edible coating was a concentration of 3% with a soaking time of 3 minutes. Soaking time, chitosan concentration, and the interaction between soaking time and chitosan concentration affected the deterioration of the quality of the skinless snapper fillets.